PENERAPAN PROSEDUR AUDIT ATAS KAS OLEH KAP HENDRAWINATA, HANNY, ERWIN & SUMARGO - Rafli Nur Hidayat (2022)
The audit procedure is one of the most important components that must be carried out by the public accounting firm (KAP) in auditing the company's financial statements. The author in carrying out field work practices (PKL) has the opportunity to audit cash accounts and cash equivalents owned by PT XYZ engaged in manufacturing. And the author will discuss more in particular the Cash Account. The purpose of conducting an audit of cash and cash equivalents is to ensure that the cash balance presented by the company as of the balance sheet date has been reasonably disclosed to the appropriate amount. The implementation of audit procedures is carried out following the audit program that has been made and in accordance with the audit standards in force in Indonesia. In conducting an audit at PT XYZ, it can be concluded that the application of audit procedures on the cash of PT XYZ conducted by the public accounting firm Hendrawinata, Hanny, Erwin & Sumargo is declared reasonable and free from material misstatements.